Asesmen Nasional sebagai Pilihan Evaluasi Sistem Pendidikan Nasional - Indahri, Yulia (Jurnal Aspirasi, 2021)
On September to November 2021, the government conducted a National Assessment (NA) as the latest evaluation to national education system. In Indonesia, the education evaluation model has undergone several changes. The most recent one, the National Examination (NE), which was still the only national student evaluation for primary and secondary school students had to be canceled in 2020 due to the pandemic. The results of the NA will be a baseline of the service and performance of each school participating in NA. Next step would be a joint reflection to accelerate the improvement of the quality of education. This paper tried to determine whether NA would be a sound decision in present day educational system evaluation. A literature review is expected to describe the dynamics and complement the academic study of the implementation of educational evaluation in a new format. From the long journey of education evaluation, all stakeholders can learn so that education evaluation does not fall back into the same trap of results-oriented without paying any attention to the process. Cost, coverage area, government's commitment as the provider, and evaluation results for the development of education units are important factors indicating that NA can be accepted as a choice taken into account from the various options available. Evaluation of the implementation of NA needs to be reported on time and accessible to the public so that any efforts could be made to resolve current and identified education problems as well as to follow the ideal of national education.AbstrakDi bulan September–November 2021, pemerintah melaksanakan Asesmen Nasional (AN) sebagai evaluasi mutakhir terhadap sistem pendidikan nasional. Model evaluasi pendidikan di Indonesia telah beberapa kali mengalami perubahan, dan terakhir di tahun 2020, Ujian Nasional (UN) yang masih menjadi satu-satunya upaya evaluasi siswa secara nasional di akhir jenjang pendidikan dasar dan menengah harus dihapuskan karena pandemi. Hasil AN akan menjadi cermin atau potret layanan dan kinerja setiap sekolah untuk selanjutnya secara bersama-sama dapat dilakukan refleksi guna mempercepat perbaikan mutu pendidikan. Tulisan ini akan melihat apakah AN merupakan pilihan tepat untuk mengevaluasi sistem pendidikan saat ini. Studi literatur diharapkan dapat menggambarkan dinamika dan melengkapi studi pelaksanaan evaluasi pendidikan dalam format baru yang sebelumnya tidak pernah digunakan di Indonesia. Dari perjalanan panjang evaluasi pendidikan, semua pemangku kepentingan dapat belajar agar evaluasi pendidikan tidak kembali terjebak hanya untuk mengejar hasil, tanpa menghiraukan proses. Faktor biaya, luas cakupan, komitmen pemerintah sebagai penyelenggara, dan hasil evaluasi untuk pengembangan satuan pendidikan menjadi faktor penting yang menunjukkan bahwa AN dapat diterima sebagai pilihan yang perlu diperhitungkan dari beragam pilihan yang ada. Evaluasi pelaksanaan AN perlu disampaikan secara cepat dan dapat diakses oleh publik agar masalah pendidikan yang teridentifikasi saat ini dapat segera dimulai untuk diselesaikan dan cita-cita pendidikan nasional dapat diwujudkan.